2017
DOI: 10.1111/ijtd.12098
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on effective coaching by those who have been coached

Abstract: Studies on coaching have largely explored effectiveness from the perspective of a coach or employing organization rather than that of the employee or coachee. There has also been a focus on ‘successful’ coaching, but little is known about unsuccessful coaching or the hindrances to achieving coaching success. Many empirical studies on training interventions have found that support and help for employees from managers and others within the workplace enhances training effectiveness and there is an assumption in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Although perceived at times as a solution for poor performance, coaching incorporates in fact a broader developmental and empowerment perspective, to the extent that it is even recognized as an organizational development intervention. Hence, consistent with other initiatives in the HRD field, it is aimed at the development of individuals, groups and organizations (Carter et al, 2017;Hamlin et al, 2008).…”
Section: Definition Of the Fieldmentioning
confidence: 73%
See 4 more Smart Citations
“…Although perceived at times as a solution for poor performance, coaching incorporates in fact a broader developmental and empowerment perspective, to the extent that it is even recognized as an organizational development intervention. Hence, consistent with other initiatives in the HRD field, it is aimed at the development of individuals, groups and organizations (Carter et al, 2017;Hamlin et al, 2008).…”
Section: Definition Of the Fieldmentioning
confidence: 73%
“…These results are in line with Graßmann and Schermuly () who found the same side effects among those ranked highest by the coachees. Similarly, Carter and colleagues (), again from the coachees’ standpoint, found that the main barriers to coaching effectiveness were issues connected to the relationship with the coach.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations